Redescription of the genus Antrosedes Reitter, 1912 (Insecta, Coleoptera, Leiodidae, Cholevinae, Leptodirini) - Čeplík, Dávid (Zootaxa, 2023)
A redescription of the genus Antrosedes Reitter, 1912 is given. An identification key for both species of the genus, as well as data on their distribution is provided.